Дослiдження мiкророзрядної системи з тангенцiальною подачею газу - Solomenko, O. V.; Prysiazhna, O. V.; Chernyak, V. Ya.; Lendiel, V. V.; Hamazin, D. K.; Martysh, Eu. V.; Kalustova, D. O.; Prysiazhnevych, I. V. (Publishing house "Academperiodika", 2019)
A microdischarge system has been studied with the use of various plasma gases. The results of emission spectroscopy and measurements of the current-voltage characteristics are reported. The discharge parameters for the vibrational and rotational levels of plasma components are determined.